Analisis Ekonomi Usaha Wanatani Di Kawasan Hutan Rakyat Kecamatan Gemarang Kabupaten Madiun - Susanto, Anang; Sulasno, Sulasno (JURNAL AGRI-TEK, 2014)
Perennials in the area of planted forest folk are usually smaller in extent than the seasonal crops planted , so the most it can do the mixing plant communities with seasonal annual plants in the same region and are on the land . , Preservation activities by managing vacant land . This study aims to : 1.Menghitung feasibility of agroforestry on public lands .2 . Knowing strata of society with the land tani.Luas wana program is divided into three strata . The division of the land area strata based on the average land ownership in Java are narrow . The third stratum : 1.Strata 1 with a land area of less than 0.25 ha of land 2.Strata 2 with 0.5 to 1 ha 3.Strata 3 land area of more than 1 ha results in this study were able , Net Present Value ( NPV ) / Net Value for strata I Rp . 14,869,064 while stratum II Rp . 8,803,698 , and for the third strata of Rp . 35,129,500 , - , Benefit Cost Ratio ( BCR ) of 5.85 for strata I , II strata of 1.37 and of 2.43 for stratum III Results for , Gain Ratio , Internal Rate of Retrun ( IRR ) of strata I 26 % while for stratum II by 38 % and for stratum III by 31 % refund Analysis Break Even Point ( BEP ) expenditures and receipts strata I can break even in year 3 , while on the second level of expenditures and receipts can break even in year 4 , and the strata III revenues and expenditures break even in 3rd.Keywords : Perennials , strata , farmers , forest land_